2018
DOI: 10.1073/pnas.1800006115
|View full text |Cite
|
Sign up to set email alerts
|

Neural reactivation in parietal cortex enhances memory for episodically linked information

Abstract: Remembering is a complex process that involves recalling specific details, such as who you were with when you celebrated your last birthday, as well as contextual information, such as the place where you celebrated. It is well established that the act of remembering enhances long-term retention of the retrieved information, but the neural and cognitive mechanisms that drive memory enhancement are not yet understood. One possibility is that the process of remembering results in reactivation of the broader episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 47 publications
9
70
1
Order By: Relevance
“…For example, recollection-responses in the left AG are heightened for trials with longer relative to shorter presentation at encoding (Vilberg & Rugg, 2009a, 2009b, a trend that we replicated ( Figure 3E). Similarly, this region has been reported to track stimulus repetition (Gilmore et al, 2015;Guerin & Miller, 2011;Nelson, Arnold, Gilmore, & McDermott, 2013), amount of source information at retrieval (Hutchinson et al, 2014), degree of cortical reinstatement from encoding (Jonker, Dimsdale-Zucker, Ritchey, Clarke & Ranganath, 2018;Kuhl & Chun, 2014;Leiker & Johnson, 2014;Thakral et al, 2017b), and subjective memory strength (Rissman et al, 2016;Thakral et al, 2015). This recent evidence is broadly consistent with the mnemonic accumulator hypothesis (Wagner et al, 2005), which states that activity in the posterior parietal cortex tracks the amount of available evidence for an old response during recognition.…”
Section: Angular Gyrus and Evidence Accumulationsupporting
confidence: 56%
“…For example, recollection-responses in the left AG are heightened for trials with longer relative to shorter presentation at encoding (Vilberg & Rugg, 2009a, 2009b, a trend that we replicated ( Figure 3E). Similarly, this region has been reported to track stimulus repetition (Gilmore et al, 2015;Guerin & Miller, 2011;Nelson, Arnold, Gilmore, & McDermott, 2013), amount of source information at retrieval (Hutchinson et al, 2014), degree of cortical reinstatement from encoding (Jonker, Dimsdale-Zucker, Ritchey, Clarke & Ranganath, 2018;Kuhl & Chun, 2014;Leiker & Johnson, 2014;Thakral et al, 2017b), and subjective memory strength (Rissman et al, 2016;Thakral et al, 2015). This recent evidence is broadly consistent with the mnemonic accumulator hypothesis (Wagner et al, 2005), which states that activity in the posterior parietal cortex tracks the amount of available evidence for an old response during recognition.…”
Section: Angular Gyrus and Evidence Accumulationsupporting
confidence: 56%
“…In parallel with above described rapid, retroactive memory enhancement, our imaging results showed transient increases in neural pattern similarity between initial learning and emotional tagging phases in the aversive (vs. neutral) condition. This similarity measure is thought to reflect the degree of reactivation of overlapping neural traces triggered by each face cue, according to previous studies assessing the similarity of neural activity between encoding and retrieval (Jonker, Dimsdale-Zucker, Ritchey, Clarke, & Ranganath, 2018;Tompary & Davachi, 2017). It is thus likely that our observed increases in neural pattern similarity after the onset of aversive (vs. neutral) voices during emotional tagging could be caused by emotion-induced autonomic arousal accompanied with elevated catecholamine release, which rapidly potentiates neuronal excitability in currently activated brain regions like the hippocampus and stimulus-sensitive neocortical regions (Rogerson et al, 2014;Zhou et al, 2009).…”
Section: Emotion-charged Reactivation Of Overlapping Neural Traces Inmentioning
confidence: 99%
“…Further, during such cued retrieval, the hippocampus showed signatures of neural reinstatement of another within-event element that was irrelevant to the given test trial (Horner, Bisby, Bush, Lin, & Burgess, 2015; for a review, see Horner & Doeller, 2017). Corrobo rating these findings, a recent study showed that retrieval improved long-term memory not only for the specific information tested but also for nontargeted information that shared the same spatial context ( Jonker, Dimsdale-Zucker, Ritchey, Clarke, & Ranganath, 2018). These results demonstrate that memories are reorganized into integrated events and provide compelling evidence that the retrieval of multiple elements of an event is mutually contingent.…”
mentioning
confidence: 99%